The Effect of Placement Exposure and Placement Prominence on Recognition, Attitude, and Travel Intention of Tourism Destination in Reality Television Show - Stacia R. Mege (Institut Pariwisata dan Bisnis Internasional, 2015)
Previous studies of tourism have proven that inclusion of destination in movies and television serials can induce tourism. This study aims to investigate the effect of destination placement in reality television show. The author will study the interaction of exposure to destination placement and the placement prominence toward recognition, attitude, and intention to visit of participants to the destination. An experimental study using videos of Korean reality show- Running Man will be run on groups of participants. The expected results are as follows. Prominent placement will be more recognized than subtle placement. Participants who will be exposed to destination placement will have higher attitude than those who don’t. And attitude is expected to mediate effect of destination placement to intention to visit. The results expected from this research will enrich the literature of product placement from two perspectives, the product (tourism destination) and the media (reality show). The result of this study will be useful for destination marketing organization to explore alternative promotional media.